2022
DOI: 10.1108/imds-01-2022-0033
|View full text |Cite
|
Sign up to set email alerts
|

Online communities and offline sales: considerations on visiting behavior dimensions and online community types

Abstract: PurposeAs an increasingly popular tool for product exploration, online communities have an important impact on consumers’ purchasing decisions. The purpose of this study is to gain a deeper understanding of how visiting behaviors in online communities affect consumers’ offline purchasing behavior. The moderating role of two dimensions of consumer visiting behaviors (visiting depth and visiting breadth) also receives attention. Moreover, the impact of consumer visiting behaviors on offline sales for different t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 86 publications
(178 reference statements)
1
1
0
Order By: Relevance
“…Therefore, price competition can mitigate the double marginal effect to a certain extent. This finding extends (Sun et al ., 2022) related research, which found that the intervention of the agency model in online channel will transfer the effect brought about by demand signal sharing. From this perspective, the behavior of price competition among members also shifts the double marginal effect brought about by information sharing.…”
Section: Comparison Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, price competition can mitigate the double marginal effect to a certain extent. This finding extends (Sun et al ., 2022) related research, which found that the intervention of the agency model in online channel will transfer the effect brought about by demand signal sharing. From this perspective, the behavior of price competition among members also shifts the double marginal effect brought about by information sharing.…”
Section: Comparison Analysissupporting
confidence: 91%
“…Although the above studies explored that the manufacturer sells the products through different modes in the online platform, they consider only how the supply chain operates on the online channel, but they ignore the traditional offline channel. It is worth noting that the offline retail environment provides a consumption environment in which consumers pay more attention to the visual experience of purchasing (Ugolkov et al ., 2020; Sun et al ., 2022). Therefore, contrary to earlier research in this field, we do not only consider the E-commerce online channel with different modes; we also introduce the competitive offline market.…”
Section: Literature Reviewmentioning
confidence: 99%